Treatment of Extramammary Paget Disease and the Role of Reflectance Confocal Microscopy: A Prospective Study. Issue 4 (April 2021) - Navarrete-Dechent, Cristian; Aleissa, Saud; Cordova, Miguel; Hibler, Brian P.; Erlendsson, Andres M.; Polansky, Max; Cordova, Frank; Lee, Erica H.; Busam, Klaus J.; Hollmann, Travis; Lezcano, Cecilia; Moy, Andrea; et al.
Abstract : BACKGROUND: Extramammary Paget disease (EMPD) poses treatment challenges. Invasive and noninvasive treatment modalities exist with variable success reported. Reflectance confocal microscopy (RCM) is emerging as an adjuvant diagnostic tool. OBJECTIVE: To evaluate the treatment of EMPD patients and the role of RCM. METHODS: Prospective study. Demographic and tumor characteristics were recorded. Handheld-RCM was performed and correlated with histology. Treatment, clearance, pathology, and follow-up were all recorded. RESULTS: Thirty-six EMPD lesions in 33 patients were included. Mean age was 71.7 years, and 23 were men. Mean number of surgical stages needed to clear margins was 1.9 (SD, 0.9; 1.0–3.0 stages), and mean margin needed to clear was 1.8 cm. Reflectance confocal microscopy correlated well with scouting punch biopsies (kappa, 0.93; p < .001). Disruption of the dermoepidermal junction was associated with invasive EMPD versus in situ (83.3% vs 25.9%) on histology ( p = .01). Limitations: Relatively small sample size. CONCLUSION: Extramammary Paget disease is challenging, and lesion demarcation is of the utmost importance. Using a staged surgical excision approach, the mean margins needed were 1.8 cm, less than previously reported. Nonsurgical modalities, including radiation therapy, imiquimod, or photodynamic therapy can be considered if surgery is not pursued. Reflectance confocal microscopy is a valuable noninvasive imaging modality for the management of EMPD. Abstract : Supplemental Digital Content is Available in the Text.